The influence of self-efficacy on career maturity in college students: mediating the moderation of creativity tendency and achievement motivation - Tong, Yuying; Zhong, Ming; Yang, Jiarun; Liu, Xiaoxuan; Yang, Daiwa; Zhao, Xueying; Hou, Yixuan (Frontiers in Psychology, 2025)
ObjectiveThis study explores the relationship between self-efficacy and career maturity among college students, while investigating the mediating role of creativity tendency and achievement motivation.MethodsA survey was conducted on 950 college students using the Self-Efficacy Scale, Career Maturity Scale, Creativity Tendency and Achievement Motivation Scale.ResultsSelf-efficacy significantly and positively predicts career maturity. Creativity tendency has a mediating effect between self-efficacy and career maturity among undergraduate students. The interaction between self-efficacy and achievement motivation significantly predicts creativity tendency, while the interaction between creativity tendency and achievement motivation significantly predicts career maturity.ConclusionCreativity tendency partially mediates the relationship between self-efficacy and career maturity. Achievement motivation moderates both the initial and later stages of the mediating pathway as “self-efficacy → creativity propensity → career maturity.”